Pandangan Ahli Gizi Tentang Pelayanan Gizi Berbasis Gen Di Indonesia : Pandangan Ahli Gizi Tentang Pelayanan Gizi Berbasis Gen di Indonesia - Putri, Sintia Aurilia; Aji, Arif Sabta; Sampurno, Edi; Aprilia, Veriani; Zulfa, Ifana Fitria; Alfiana, Rina; Hafizhah, Rafiqah Dwita; Farhan, Alfina Ulfah; Surendran, Shelini (Amerta Nutrition, 2023)
Background: Cardiometabolic diseases are principal contributors to mortality, morbidity, and healthcare costs. Additionally, many Single Nucleotide Polymorphisms (SNPs) have been associated with cardiovascular health outcomes. Nutrition professionals' perspectives on genetic-based nutritional services play a pivotal role in treating and preventing non-communicable diseases (NCDs). Objectives: This study aims to explore Indonesian nutritionists' viewpoints on gene-based nutrition services. Methods: Employing a qualitative phenomenological approach, six Indonesian nutritionists from key provinces (DKI Jakarta, West Java, Central Java, East Java, and DI Yogyakarta) participated in in-depth interviews. Themes encompassed nutritionists' views on gene-based nutrition's role in NCD prevention, genetics science, and genetic testing understanding. Thematic analysis was performed using Nvivo v.12. Results: Results showed that nutritionists had a substantial understanding of genetics and gene-based nutrition services, despite concerns about test costs. They comprehended gene-based nutrition's role in NCD prevention and acknowledged its significance in preventing NCDs. Conclusions: Within this study, Nutritionists express the importance of gene-based nutrition services in NCD prevention. To enhance engagement, nutritionists are encouraged to communicate genetic testing's value to the community. This dissemination will help advance  NCD prevention efforts.